2012
DOI: 10.6061/clinics/2012(09)17
|View full text |Cite
|
Sign up to set email alerts
|

Exercise alleviates hypoalgesia and increases the level of calcitonin gene-related peptide in the dorsal horn of the spinal cord of diabetic rats

Abstract: OBJECTIVE:The aim of this study was to evaluate the effects of treadmill training on nociceptive sensitivity and immunoreactivity to calcitonin gene-related peptide in the dorsal horn of the spinal cord of diabetic rats.METHODS:Male Wistar rats were divided into three groups: control, diabetic and trained diabetic. Treadmill training was performed for 8 weeks. The blood glucose concentrations and body weight were evaluated 48 h after diabetes induction and every 30 days thereafter. The nociceptive sensitivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
(36 reference statements)
0
3
0
Order By: Relevance
“…Meanwhile, the immunohistochemical procedure and optical densitometry were performed to measure the level and intensity of CGRP. The results showed that exercise reduced the hyperalgesia and reversed the diabetes-induced decrease in CGRP in the DRG levels of diabetic rats ( Nascimento et al, 2012 ). Therefore, the exercise mechanism for nociceptive hyperalgesia may be increase in CGRP, which reverses the pancreatic β-cell death induced by oxidative and ER stresses through ASK1, p38 MARK, and ERK1/2.…”
Section: Mechanisms Of Exercise In Improving Diabetic Neuropathic Painmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, the immunohistochemical procedure and optical densitometry were performed to measure the level and intensity of CGRP. The results showed that exercise reduced the hyperalgesia and reversed the diabetes-induced decrease in CGRP in the DRG levels of diabetic rats ( Nascimento et al, 2012 ). Therefore, the exercise mechanism for nociceptive hyperalgesia may be increase in CGRP, which reverses the pancreatic β-cell death induced by oxidative and ER stresses through ASK1, p38 MARK, and ERK1/2.…”
Section: Mechanisms Of Exercise In Improving Diabetic Neuropathic Painmentioning
confidence: 99%
“…Therefore, the mechanism of apoptosis associated with CGRP is involved in the pathological mechanism of DNP. An STZ injection-induced diabetic rat model was established by Nascimento et al (2012) to research on the role of exercise in DNP and CGRP levels in DRG. A tail-flick apparatus was used to assess nociceptive injury changes.…”
Section: Mechanisms Of Exercise In Improving Diabetic Neuropathic Painmentioning
confidence: 99%
“…Thus, these studies implied that patients with DNP, by performing proper exercises, could have a better internal glucose level control. Treadmill exercise in rat models with DNP was also found to be beneficial in relieving DNP by increasing NO synthesis [ 71 ] and regulating apoptosis [ 72 ], etc.…”
Section: Treatments Against Dnpmentioning
confidence: 99%